Implementasi Pramuka Prasiaga: Menanamkan Nilai-Nilai Kebersamaan di RA Al-Azhar Palangka Raya - Bismillah, Alfi; Muzakki; Arumawati, Nur Sani; Nurwie (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The Pramuka Prasiaga activities at RA Al-Azhar Palangka Raya aim to instill values of togetherness and develop social and emotional skills in early childhood. Through a qualitative approach with a participatory method, this program engages children in various enjoyable play activities. Observations indicate that children are very enthusiastic and actively participate, reflecting the effectiveness of play-based learning methods. Although there are challenges, such as children who lack self-confidence, these activities have a positive impact on the character development of the children. This research recommends the importance of continuous evaluation and improvement to create a more inclusive and supportive learning environment.